126 Objective Functional Outcome Measures Expose Relevant Ceiling Effects Inherent to Subjective Patient-Reported Outcome Measures in Patients Undergoing Surgery for Lumbar Degenerative Disorders. (April 2023) - Maldaner, Nicolai; Zeitlberger, Anna; Ziga, Michal; Bozinov, Oliver; Regli, Luca; Stienen, Martin N.
Abstract : INTRODUCTION: Patient-reported outcome measures (PROMs) may be subject to relevant floor and ceiling effects which may induce substantial bias to the outcome assessment after spine surgery. METHODS: In a prospective study, 50 patients were assessed preoperatively, 6-weeks and 3-months postoperatively for objective functional impairment using the smartphone-based 6-minute walking test (6WT) as well as a set of widely used PROMs. Paired sample t-tests were used to establish significant difference between the changes in raw 6-minute walking distance (6WD) and PROMs at baseline, 6-weeks and 3-months follow-up. Floor and ceiling effect were considered present if >15% achieved the worst and best status. Pearson correlation coefficients were used to define the relationship between 6WT and PROMs at 6-weeks and 3-months. RESULTS: The mean 6WD improved from 377 m preoperative to 490 m and 517 m at 6-weeks and 3-months follow-up (p < 0, 05). While all PROMs improved from pre- to six-week postoperative, no significant improvement was observed beyond the 6-weeks follow up in the Core Outcome Measure Index (COMI), the Zurich Claudication Questionnaire (ZCQ) Symptoms Severity Scale, the ZCQ Physical Performance Scale, VAS Back and Leg pain. A ceiling effect was observed for the COMI, the ZCQ Symptoms Severity Scale, the ZCQ Physical Performance Scale, VAS back and VAS leg pain in 2%, 4%, 24%, 20% and 16% of patient at the 6-weeks follow up. Correlation between the 6WD and PROMs significantly increased from the 6-weeks to 12-weeks follow up. CONCLUSIONS: PROMs reach their best possible score in a relevant number of patients early after surgery for DLD while objective functional outcome continues to improve beyond the 6-weeks follow-up. Objective measures of function may expose relevant ceiling effects observed by PROMs and describe the continued recovery of patient.